2010
DOI: 10.1111/j.1939-0025.2010.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to survive: Sexual assault, poverty, and mental health outcomes of African American women.

Abstract: A substantial body of research documents the mental health consequences of sexual assault including, but not limited to, depression, posttraumatic stress disorder (PTSD), substance use, and suicidality. Far less attention has been given to the mental health effects of sexual assault for ethnic minority women or women living in poverty. Given African American women’s increased risk for sexual assault and increased risk for persistent poverty, the current study explores the relationship between income and mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 90 publications
7
68
0
Order By: Relevance
“…Moderate to high rates of SV (e.g., 22%–100%) are reported in various samples of predominantly African American women, including substance abuse treatment recipients (Young & Boyd, 2000), low-income samples (Boyd, Henderson, Ross-Durow, & Aspen, 1997; Bryant-Davis et al, 2010; Dailey, Humphreys, Rankin, & Lee, 2011; Kalichman, Williams, Cherry, Belcher, & Nachimson, 1998), and military veterans (Campbell, Greeson, Bybee, & Raja, 2008). …”
Section: Health Risks and Adverse Conditions For African American Wommentioning
confidence: 99%
See 4 more Smart Citations
“…Moderate to high rates of SV (e.g., 22%–100%) are reported in various samples of predominantly African American women, including substance abuse treatment recipients (Young & Boyd, 2000), low-income samples (Boyd, Henderson, Ross-Durow, & Aspen, 1997; Bryant-Davis et al, 2010; Dailey, Humphreys, Rankin, & Lee, 2011; Kalichman, Williams, Cherry, Belcher, & Nachimson, 1998), and military veterans (Campbell, Greeson, Bybee, & Raja, 2008). …”
Section: Health Risks and Adverse Conditions For African American Wommentioning
confidence: 99%
“…In a U.S. national sample, a history of SV has been found to be associated with anxiety disorders, mood disorders, PTSD, SUDs, and suicide attempts (Iverson et al, 2013). Studies focusing on the mental and behavioral health of African American female SV survivors in particular are limited, and the studies that exist usually rely on urban, low socioeconomic status (SES), or drug-abusing samples (Boyd et al, 1997; Bryant-Davis, Chung, & Tillman, 2009; Bryant-Davis et al, 2010; Campbell et al, 2008; Vaszari, Bradford, CallahanO'Leary, Ben Abdallah, & Cottler, 2011). For example, in a community sample of low-income, ethnically diverse women ( N = 835), Temple and colleagues (2007) found that sexual assault by current partners and nonpartners was a significant predictor of PTSD symptoms for African American women.…”
Section: Health Risks and Adverse Conditions For African American Wommentioning
confidence: 99%
See 3 more Smart Citations